FACTORS AFFECTING DELAYS IN THE CONSTRUCTION PROJECT OF 5 FLOOR PARKING BUILDING ROEMANI HOSPITAL, SEMARANG. - nugraha, agra febyola lova; Lathif, Busyro; Suwandi, Putri Anggi Permata; Husodo, Ibnu Toto (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
In the planning of a project, there have to be a time schedule that can served as a guideline in the project, this shows that scheduling can influence the activity of a project. A good time schedule in a project can make project run effectively and efficiently, but in reality the actual work of a project did not always go as planned. In this case, the construction of library of UIN Sunan Ampel Surabaya.In the process of construction of library of UIN Sunan Ampel Surabaya, there is a delay that caused by a lot of factors, resulting in a delay of 49 days, the project initial duration is 154 days but the implementation duration is 203 days. Because of this, an analysis was carried out on this matter to determine what caused this lateness on project scheduleFrom the analysis that has been done the result is that the project lateness is caused in preparation work and the usage of work system with 3 shift but using the same man power. Factors of this lateness is caused by the owner, the conctractor, and weather disturbance.